2015
DOI: 10.1891/1946-6560.6.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Knowledge Concerning the Safe at Home Instrument for Assessing Readiness to Change Among Individuals in Batterer Treatment

Abstract: The Revised Safe at Home instrument (Begun et al., 2008) is based on application of the transtheoretical model of behavior change (TMBC) and offers clinicians and clients an assessment tool to measure client readiness for changing intimate partner violence (IPV) behaviors. Scale scores from this tool can be used to assess client readiness to change and evaluate treatment program outcomes. The purposes of this study are to relate patterns in scale scores with those obtained in previous studies, across the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…In Northern California, one BIP reported more or less equal rates of physical and verbal abuse across gender (Hamel, Ferreira, & Buttell, 2015). Comparable scores have been reported between male and female offenders by other researchers on the Safe at Home instrument, which measures readiness to change (Sielski et al, 2015); on the PAS, a predictor of verbal and physical abuse (Carney & Buttell, 2004a); and on measures of emotional abuse and control (Hamel, Jones, et al, 2015;Kernsmith, 2005). However, it should be noted that when fear has been examined in BIP clients, women report experiencing more fear of their violent partners than do men (Ross, 2012).…”
Section: Studies With Related Populations That Have Reduced Physical mentioning
confidence: 73%
See 1 more Smart Citation
“…In Northern California, one BIP reported more or less equal rates of physical and verbal abuse across gender (Hamel, Ferreira, & Buttell, 2015). Comparable scores have been reported between male and female offenders by other researchers on the Safe at Home instrument, which measures readiness to change (Sielski et al, 2015); on the PAS, a predictor of verbal and physical abuse (Carney & Buttell, 2004a); and on measures of emotional abuse and control (Hamel, Jones, et al, 2015;Kernsmith, 2005). However, it should be noted that when fear has been examined in BIP clients, women report experiencing more fear of their violent partners than do men (Ross, 2012).…”
Section: Studies With Related Populations That Have Reduced Physical mentioning
confidence: 73%
“…For instance, progress toward reducing frequency of physical and nonphysical abuse behaviors can be assisted with administration of either the Revised Conflict Tactics Scales (CTS2) or the original Conflict Tactics Scales in combination with a validated measure of emotional abuse and control, such as the Controlling and Abusive Tactics (CAT) Questionnaire (Hamel, Jones, Dutton, & Graham-Kevan, 2015), the Multidimensional Measure of Emotional Abuse (MMEA; Murphy & Hoover, 2001), or the Measure of Psychologically Abusive Behaviors (MPAB; Follingstad, 2011). Other useful instruments include the Safe at Home questionnaires based on the transtheoretical stages of change theory, which gauges a client's willingness to change and take responsibility for his or her behavior (Sielski, Begun, & Hamel, 2015); the Experiences in Close Relationships Questionnaire-Revised (ECR-R; Fraley, Waller, & Brennan, 2000), useful for identifying insecure romantic attachment (fear of abandonment or avoidance of intimacy); and the Reasons for Violence Scale, which identifies both expressive and instrumental motives among offenders (G. L. Stuart, Moore, Gordon, Hellmuth, et al, 2006).…”
Section: Assessment Protocol and Instrumentsmentioning
confidence: 99%
“…Still, Feder and Henning (2005) found equal rates of both minor and severe physical assaults, injuries inflicted, and use of alcohol or drugs in their sample of dually arrested couples, and the female respondents in a survey of BIPs in Rhode Island and California reported higher rates of both emotional and physical PA in comparison to their male counterparts as well as similar motives (Elmquist et al, 2014). Other researchers have reported comparable scores between male and female offenders on measures of emotional abuse and control (Hamel, Jones, Dutton, & Graham-Kevan, 2015; Kernsmith, 2005), readiness to change (Sielski, Begun, & Hamel, 2015), and propensity for abusiveness (Carney & Buttell, 2004) and have developed similar typologies (Babcock, Miller, & Siard, 2003). The one study that investigated the effectiveness of BIPs for female perpetrators found it as effective as similar programs for men (Carney & Buttell, 2006).…”
Section: Introductionmentioning
confidence: 97%